1991
DOI: 10.3758/bf03199571
|View full text |Cite
|
Sign up to set email alerts
|

Generating makes words memorable, but so does effective reading

Abstract: In many experiments, memorial benefits have been found when subjects generate items from fragments rather than read items in their complete forms. Does generation cause this difference, or are subjects disposed to adopt different strategies when generating as opposed to reading? If generating causes the difference, items processed in the same way apart from a generative stage should therefore benefit from that generative stage. Our experiments did result in benefits for generating as opposed to reading, but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
89
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 35 publications
(51 reference statements)
11
89
3
Order By: Relevance
“…As was expected, requiring item-by-item JOLs eliminated the usual perceptual interference effect in free recall, just as occurs with the generation manipulation (Begg et al, 1991;Matvey et al, 2001). Even though the sample consists of 16 participants, the post hoc power analysis suggests that the sample size is reasonable to obtain a significant difference between the two conditions.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…As was expected, requiring item-by-item JOLs eliminated the usual perceptual interference effect in free recall, just as occurs with the generation manipulation (Begg et al, 1991;Matvey et al, 2001). Even though the sample consists of 16 participants, the post hoc power analysis suggests that the sample size is reasonable to obtain a significant difference between the two conditions.…”
Section: Resultsmentioning
confidence: 79%
“…Research on a related phenomenon, the generation effect, shows this. If a JOL is made after each word, the typical generation effect (greater memory for generated than for read words) is not found (Begg, Vinski, Frankovich, & Holgate, 1991;Matvey et al, 2001). Two reasons are proposed in the literature for this.…”
Section: Methodsmentioning
confidence: 99%
“…Or perhaps the difficult questions induced subjects to engage in more test-appropriate processing of the read items. Begg et al (1991) found that when read items were processed in a meaningful way, the generation effect was eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous research had demonstrated that the process oftrying to answer the question is the important determinant of memory performance. In fact, a generation advantage was found after an attempt to generate an answer regardless of whether or not the subject produced the answer (Begg, Vinski, Frankovich, & Holgate, 1991;Pressley, McDaniel, Turnure, Wood, & Ahmad, 1987;Slamecka & Fevreiski, 1983). Begg and his colleagues typically required a subject-in the generate conditionto attempt to generate a solution, and if the subject failed, they provided the subject with the intact answer.…”
mentioning
confidence: 99%
“…Begg, Vinski, Frankovich, and Holgate (1991), for example, showed that generation advantages could be eliminated by giving participants effective strategies, such as imagery, to use when encoding to-be-read items. Similarly, deWinstanley and Bjork (1997) eliminated a previously observed generation advantage by giving participants explicit instructions concerning the type of retention test to expect and how to process information optimally in anticipation of such a test.…”
mentioning
confidence: 99%